Pembelajaran Kontekstual Dalam Kegiatan Bahtsul Masail Santri Di Pondok Pesantren Al-Muhibbin Bahrul Ulum Tambakberas Jombang - M. Syarif Hidayatulloh (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2018)
Pesantren is the oldest Islamic education institution in Indonesia that grows and develops along with the development of Islam in Indonesia. Bahstul masail is one of the learning methods found in the pesantren environment. This method educates students to practice critical , solutive and contextual thinking. While contextual learning or CTL (Contextual and Teaching Learning) is a modern learning approach that emphasizes students as learning subjects who explore and seek their own experiences to gain knowledge. This study discusses about the process of learning activities including students at the Islamic boarding school Al-Muhibbin Bahrul Ulum Tambakberas Jombang? Is the activity of the Islamic boarding school students at Islamic boarding school Al-Muhibbin Bahrul Ulum Tambakberas Jombang an application of contextual learning? This study uses a qualitative-descriptive method. The data source; 1. Written 2. Documentation 3. Field. For data collection techniques through interviews, participation, and documentation. The results of this study are the activities of students in the al-Muhibbin Islamic boarding school is an extra scientific activity which is attended by all levels of students and is done once a month with the aim of training students to analyze and provide answers to legal problems that occur in the surrounding community. Second, the activity of masap bahstul is a form of implementation of contextual learning approach method